(untitled) (Journal of Parents and Teachers, 2023)
If we stop for a moment in the current work of the school counselor, we soon detect the plurality of tasks that are contained in each one of the demands that we must attend to. We work with students, families and teachers. Cases are referred to us that are related to academic and professional orientation, psychosocial and family difficulties, psychological disorders, cognitive difficulties, etc. It is a precious multifunction work that is not easy to cover and that supposes attending to the wide diversity that we find in our classrooms.